Rebuilding The Brand Image: A Case Study Of Pr Strategies In Rebranding Atlas Beach Fest In Bali - Kadek Devi Kalfika Anggria Wardani; Ni Ketut Ayu Astiti; Anak Agung Ngurah Eddy Supriyadinata Gorda (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Public relations (PR) plays a vital role in brand recovery following reputational crises. This study examines the strategic use of PR in the rebranding of Atlas Beach Fest, a Bali-based tourism destination formerly associated with the Holywings controversy. Addressing the lack of research on PR-driven brand restoration in Southeast Asia, the study investigates how communication strategies were used to rebuild public trust. Using a qualitative case study approach, data were collected through interviews, observation, and document analysis. Findings show that efforts such as brand renaming, logo redesign, media outreach, influencer collaboration, and CSR activities effectively reshaped public perception and repositioned the brand. The study highlights the importance of integrated, communication-based PR in navigating post-crisis image transformation and offers insights into how organizations can regain legitimacy through symbolic and strategic messaging.